2008
DOI: 10.1266/ggs.83.111
|View full text |Cite
|
Sign up to set email alerts
|

The functional analysis of YabA, which interacts with DnaA and regulates initiation of chromosome replication in Bacillus subtils

Abstract: The initiation of bacterial chromosome DNA replication and its regulation are critical events. DnaA is essential for initiation of DNA replication and is conserved throughout bacteria. In Escherichia coli, hydrolysis of ATP-DnaA is promoted by Hda through formation of a ternary complex with DnaA and DnaN, ensuring the timely inactivation of DnaA during the replication cycle. In Bacillus subtilis, YabA also forms a ternary complex with DnaA and DnaN, and negatively regulates the initiation step of DNA replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 38 publications
7
79
0
Order By: Relevance
“…2A and 3 and Table 2). In addition to oriC, there were four predominant regions, along with yqeG-sda, detected in the ChIPchip experiments, which is consistent with previous results (3,11,25). There was an approximately 2-to 4-fold increase in the association of DnaA with the secondary chromosomal regions, and a greater increase in association near oriC, during replication stress compared to that during exponential growth (Table 2).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2A and 3 and Table 2). In addition to oriC, there were four predominant regions, along with yqeG-sda, detected in the ChIPchip experiments, which is consistent with previous results (3,11,25). There was an approximately 2-to 4-fold increase in the association of DnaA with the secondary chromosomal regions, and a greater increase in association near oriC, during replication stress compared to that during exponential growth (Table 2).…”
Section: Resultssupporting
confidence: 90%
“…DnaA binds to specific sites located in many chromosomal regions, some of which are in transcriptional regulatory regions and affect gene expression (3,9,18,22,25,62). Several of the regions bound by DnaA are readily detected by ChIP-chip (3) and the analogous ChAP-chip (11,25). Virtually all of these regions were associated with DnaD and DnaB (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…YabA negatively regulates replication initiation through its interactions with the ␤ clamp and DnaA (12,29,52). Mutations in YabA have been constructed that alter both interaction with DnaA and the ␤ clamp (12,29,52); however, the site on the ␤ clamp that YabA binds is unknown. In this work, we found that overexpression of YabA led to an increase in mutagenesis, which is MMR dependent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ␤ clamp is responsible for coordinating many activities at the replication fork. Also, the ␤ clamp interacts with YabA, a negative regulator of replication initiation in B. subtilis (12,27,29,52). Overexpression of the YabA protein causes a decrease in replication initiation, and deletion of yabA increases replication initiation (12,29,52) (Fig.…”
Section: Dnan5(g73r)mentioning
confidence: 99%
See 1 more Smart Citation